India Assessment 2002 Water Supply and Sanitation A WHO-UNICIEF Sponsored Study - Planning Commission (Planning Commission, 2002)
The assessment report by WHO and UNICEF provides a comprehensive overview of water supply and sanitation in India. Conducted as a collaborative effort involving the Planning Commission of India, it aims to evaluate existing challenges and recommend actions for improvement in the sector. India has rich water resources, but uneven distribution and pollution are significant challenges. While the country receives about 4,000 billion cubic meters of rainfall annually, it faces scarcity due to high demands from growing urbanization, population increases, and environmental degradation. Groundwater depletion is a critical concern, and water quality issues—including contamination from heavy metals, nitrates, and pathogens—greatly hinder public health.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Urban Sanitation; Rural Water Supply; Health Impact; National Water Policy (2002); Government Initiatives; The Midnapur Model; Surat’s Transformation; Community Participation; Cross-Sector Coordination; Infrastructure Development